Correlation Study of Enculturations Surah Ash Shaff: 10-11 with Spiritual Quotient A Case Study - Hutasuhut, Julianto; Saragih, Al Kausar (Universitas Malikussaleh, 2020)
In an effort to create a national cultural agenda of